2010
DOI: 10.1016/j.bpc.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spectral tuning in monomeric teal fluorescent protein mTFP1

Abstract: We present results of theoretical studies of the variants of the monomeric teal fluorescent protein from Clavularia coral (mTFP1) which present promising members from the GFP family. Predictions of quantum chemical approaches including density functional theory and semiempirical approximations are presented for the model systems which mimic the chromophores in different environments. We describe the excitation energy spectrum of the cyan mTFP1 fluorescent protein with the original chromophore and with chromoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…For the systems with carefully optimized geometry parameters, ZINDO has been found to be very efficient in computing bands in optical spectra. As shown in our previous applications for several classes of fluorescent proteins [19,21,24], such a strategy in fact leads to accurate results that are comparable to the experimenttal values. In this work we show that an elaborate selection of model clusters in the coordinate-locking scheme and an application of fairly inexpensive quantum chemistry methods allow us to calculate bands both in the absorption and in the emission spectra of proteins.…”
Section: Introductionsupporting
confidence: 64%
“…For the systems with carefully optimized geometry parameters, ZINDO has been found to be very efficient in computing bands in optical spectra. As shown in our previous applications for several classes of fluorescent proteins [19,21,24], such a strategy in fact leads to accurate results that are comparable to the experimenttal values. In this work we show that an elaborate selection of model clusters in the coordinate-locking scheme and an application of fairly inexpensive quantum chemistry methods allow us to calculate bands both in the absorption and in the emission spectra of proteins.…”
Section: Introductionsupporting
confidence: 64%
“…Finally, we comment that the structure and charge of the nearby residues play a strong role in shifting the absorption wavelength to the red, compared to that in the isolated chromophore—from 408 to 437 nm. In previous studies of green and blue fluorescent proteins,23–25 we usually observed such shifts within 10–15 nm.…”
Section: Resultsmentioning
confidence: 69%
“…Following our previous experience in simulation structure and spectra of fluorescent proteins,23–25 we optimized ground state equilibrium geometry parameters in the large molecular cluster, mimicking a chromophore‐containing pocket by using density functional theory (DFT) approximations. We believe that the QM part considered in Ref 14.…”
Section: Introductionmentioning
confidence: 99%
“…To compute vertical excitation energies from the respective minima on the S 0 potential surfaces of the model systems we applied the semiempirical ZINDO method [9]. As shown previously [5][6][7][8], this strategy to estimate the S 0 -S 1 excitation energies at the DFT-optimized equilibrium geometry parameters performs quite well for these model systems.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Kindling phenomenon of KFP was successfully used for the development of novel subdiffraction method of fluorescent microscopy with resolution up to 50-100 nm As demonstrated in our previous simulations for GFP and blue fluorescent proteins [5][6][7][8], we can rely on ab initio and semiempirical methods of quantum chemistry to calculate equilibrium geometry configurations of the molecular cluster mimicking the chromophore molecule and the immediate protein environment in the ground electronic state and to estimate vertical excitation energies of the S 0 -S 1 optical transitions. The latter may be compared to the observed bands in absorption spectra of the fluorescent proteins.…”
Section: Introductionmentioning
confidence: 95%